KEJAHATAN PIDANA KHUSUS KORUPSI DI INDONESIA PERSPEKTIF HUKUM ISLAM PROGRESIF DALAM INTEGRITAS HUKUM NASIONAL - Fatakh, Abdul (IAIN Sultan Amai Gorontalo, 2015)
Corruption is a crime enormous harm to the community and it is an issue that needs serious treatment by law enforcement. This paper discusses the perspective of a progressive Islamic law in the integrity of national law against corruption. This paper analyzed the approachs of national law and Islamic law. The results showed that law enforcement corruption in the legal review of progressive Islam begins with awareness and understanding of modernization. Awareness of the system of political and economic laws, officers, the public, and anyone, so as to integrate its values on positive law and can directly change the character of the personality of the soul and mind personalized Muslim-majority Indonesia are Muslim, so it will bear legal certainty, usefulness Indonesian law and justice in a truly progressive of the Quran and the Sunnah of the Prophet.